Spectrophotometric Determination of lisinopril dihydrate using dye bleaching method in pure and pharmaceutical drugs - Shallal, Abdullah D; Albazzaz, Abdullah T; Jasim, Nabaa M; Azabo, Narsi L; Ahmad, Elaaf A; Ǩhudhur, Maysoon M; Nejres, Aws M (University of Zawia Journal of Natural Sciences, 2025)
Through oxidizing Lisinopril dihydrate (LIS) with known excess N-bromosuccinimide (NBS) as an oxidizing agent, a spectrophotometric method based on the bleaching of 5,5′-indigo disulfonic acid sodium salt (IG) dye in an acidic medium is presented. This method is accurate, straightforward, and precise. The oxidizing agent residue functions as a bleach for the sodium salt (IG) color 5,5′-indigodisulfonic acid. After the experimental conditions were optimized, the dye's intensity was measured at 610 nm. Beer’s law was applied to the proposed method, and it was valid within a concentration range of 2.5–50 μg/mL, and the linear regression was R2 = 0.9968. The limit of quantitation was 2.5 μg/mL, and the molar absorptivity coefficient (ε) 1.8985×103 L/mol.cm, Sandell's sensitivity was 0.2325 μg/ . The tablet's excipients don't interact with anything. The current method worked well for determining the amount of lisinopril (LIS) in tablet formulation, with mean recoveries ranging from 98.24 to 102.1 per cent. The student’s t-and-F-test were used to statistically compare the data with those of a standard reference